Analisis Kinerja Pemerintah Daerah Menggunakan Data Envelopment Analysis (DEA) dalam Perspektif Audit Kinerja - Mutmainna Sarita Bandaso; Junaidi Junaidi; Rahmawati Rahmawati (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2026)
This research analyzes the performance of local governments in Luwu Raya using the Data Envelopment Analysis (DEA) method from a performance audit perspective. With input variables such as Budget Realization Reports, the number of Civil Servants and Public Service Units, and output variables like Economic Growth and poverty rates, DEA is used to measure the relative efficiency between Decision Making Units (DMUs), in this case, local governments in the Greater Luwu area. The research results show that most local governments have been able to manage resources efficiently, leading to significant economic growth and a decrease in poverty rates. This indicates that budget allocation, optimization of civil servant performance, and the role of public service units contribute significantly to achieving regional development goals. This finding also shows that the DEA approach can be an effective tool in supporting performance audits, as it is able to provide an objective overview of local governments' success in achieving the principles of economy, efficiency, and effectiveness (value for money). This research is expected to strengthen the literature on public sector performance evaluation while providing practical recommendations for both central and local governments to maintain and improve the positive achievements that have been made